2019
DOI: 10.1016/j.ijscr.2019.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocardial infarction following penetrating thoracic trauma: A case report and review of literature

Abstract: HighlightsAMI as a result of penetrating thoracic trauma is rare, but can occur secondary to an acute thrombus, even in the absence of a direct cardiac injury.Regardless of the cause of AMI, medical management should follow current guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Acute myocardial infarction (AMI) is a heart disease, whose pathogenesis is that persistent myocardial ischemia and hypoxia are caused by interruption or decline in coronary blood flow due to various factors based on the coronary artery disease, ultimately leading to myocardial cell necrosis, usually accompanied by such clinical complications as cardiac insufficiency and heart failure [1] [2] . With the intensification of population aging in China in recent years, the morbidity rate of AMI has increased year by year, making AMI one of the common diseases causing death and affecting the quality of life [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Acute myocardial infarction (AMI) is a heart disease, whose pathogenesis is that persistent myocardial ischemia and hypoxia are caused by interruption or decline in coronary blood flow due to various factors based on the coronary artery disease, ultimately leading to myocardial cell necrosis, usually accompanied by such clinical complications as cardiac insufficiency and heart failure [1] [2] . With the intensification of population aging in China in recent years, the morbidity rate of AMI has increased year by year, making AMI one of the common diseases causing death and affecting the quality of life [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Bhuller et al have reported a case of penetrating chest injury which damaged the lung (remedied by wedge resection), however as the patient came out of OR, developed an Acute STEMI of inferolateral wall, due to a thrombus necessitating angiography and thrombus extraction. 2 These injuries can cause rupture/laceration of the lungs resulting in pneumothorax, pleural effusion and collapse. The heart may also be involved in such traumatic events, resulting in laceration or tearing of the myocardium, septal defects, free wall rupture or pericardial effusion (leading to tamponade).…”
Section: Introductionmentioning
confidence: 99%